The Use of Panoramic and Cephalometric Images to Guide Needle Placement for Inferior Alveolar Nerve Block in 7- to 12-Years-Old Children - Forough Akbari; Taraneh Zeynalzadeh Ghoochani; Adel Sharifi-Rayeni; Mahshid Sadat Hosseini; Amin Askary (Wolters Kluwer Medknow Publications, 2019)
Introduction: Pain management is one of the most important aspects of behavioral controlling in pediatric dentistry. Local anesthesia by inferior alveolar nerve block (IANB) is the primary method used for pain controlling in pediatric dentistry, and access to the mandibular foramen is the prerequisites for the success of this technique. However, the position of the mandibular foramen relative to the occlusal plane is not the same in all individuals. The aim of this study was to evaluate the effect of age and vertical facial dimension on the relative location of mandibular foramen in children aged 7 to 12 years using panoramic and cephalometric images. Materials and Methods: In this descriptive-analytical study, the cephalometric and panoramic images archived in Zahedan Faculty of Dentistry, belonging to 150 patients aged 7 to 12 years, were analyzed. Based on cephalometric analysis, these images were divided into three groups of short, normal, and long in terms of facial height, and they were divided into three age groups as well. With the help of panoramic radiography, position of the mandibular foramen was studied from different directions. The association of age and vertical facial dimension with the location of mandibular foramen was studied through ANOVA analysis and Kruskal-Wallis test. Kolmogorov-Smirnov test was used for checking the normality. Results: The results indicated that the mean and standard deviation of the anterior-posterior position of mandibular foramen (P = 0.201), the distance between the foramen and the edge of the condyle (P = 0.217), and the distance from the lower edge of the mandible (p = 0.051) showed no significant difference in all age groups. However, the mandibular foramen distance from the occlusal plane in patients aged 7 to 8 years was significantly less than in patients in the age group of 9 to 10 and 11 to 12 years (P < 0.001). Moreover, no significant difference in any of the variables under study was found between the short, normal, and long face groups (P > 0.05). Conclusion: According to the findings of this study, the needle should be inserted directly on the opposite side of the occlusal plane for the IANB anesthesia in case of children 7 to 8 years old. In other older age groups, the needle should be inserted parallel to the occlusal plane at a distance of 2 mm.